Staphylococcus aureus enterotoxin A (SEA) stimulates STAT3 activation and IL-17 expression in cutaneous T-cell lymphoma - Willerslev-Olsen, Andreas; Krejsgaard, Thorbjørn; Lindahl, Lise M; Litvinov, Ivan V; Fredholm, Simon; Petersen, David L; Nastasi, Claudia; Gniadecki, Robert; Mongan, Nigel P; Sasseville, Denis; Wasik, Mariusz A; Bonefeld, Charlotte M; et al. (American Society of Hematology, 2016)
Cutaneous T cell lymphoma (CTCL) is characterized by proliferation of malignant T cells in a chronic inflammatory environment. With disease progression, bacteria colonize the compromised skin barrier and half of CTCL patients die from infection rather than from direct organ involvement by the malignancy. Clinical data indicate that bacteria play a direct role in disease progression, but little is known about the mechanisms involved. Here, we demonstrate that bacterial isolates containing staphylococcal enterotoxin-A (SEA) from the affected skin of CTCL patients, as well as recombinant SEA, stimulate activation of STAT3 and up-regulation of IL-17 in immortalized and primary patient-derived malignant and non-malignant T cells. Importantly, SEA induces STAT3 activation and IL-17 expression in malignant T cells when co-cultured with non-malignant T cells indicating an indirect mode of action. In accordance, malignant T cells expressing a SEA non-responsive T cell receptor V beta chain (TCR-Vb) are non-responsive to SEA in mono-culture, but display strong STAT3 activation and IL-17 expression in co-cultures with SEA-responsive, non-malignant T cells. The response is induced via IL-2Rg cytokines and a Janus kinase 3 (JAK3) - dependent pathway in malignant T cells and blocked by Tofacitinib, a clinical-grade JAK3 inhibitor. In conclusion, we demonstrate that SEA induces cell cross-talk-dependent activation of STAT3 and expression of IL-17 in malignant T cells suggesting a mechanism where SEA-producing bacteria promote activation of an established oncogenic pathway previously implicated in carcinogenesis.